Juridical Implications of Power of Attorney Imposing Mortgage as Collateral in Credit Agreements at Regional Bank Public Company - Agustina, Dadan Hardiana; Djunaedi, Djunaedi (Jurnal Konstatering, 2022)
The purpose of this study is to analyze: 1) the implementation of credit agreements using a Power of Attorney to impose Mortgage as collateral in a Regional Public Company BPR Bank Brebes. 2) The juridical implications of the Power of Attorney to impose Mortgage which are used as collateral in the credit agreement at the Regional Public Company BPR Bank Brebes. The approach method used in discussing this research problem is a sociological juridical approach. The research specification used is descriptive analytical research. This type of data uses primary and secondary data. The data analysis method used in this research is qualitative data analysis. The results of the study concluded: 1). The implementation of a credit agreement using a Power of Attorney to impose Mortgage as collateral in a Regional Public Company BPR Bank Brebes is only carried out if absolutely necessary and the mortgagee cannot be present before a Notary/PPAT. The power of attorney must be given directly by the giver of the Mortgage and must meet the requirements that have been set. 2) The juridical implications of the Power of Attorney to impose Mortgage which are used as collateral in the credit agreement at the Regional Public Company BPR Bank Brebes are related to the SKMHT guarantee which cannot be withdrawn or cannot be terminated for any reason, except because the power of attorney has been exercised or because the time is up. SKMHT concerning Mortgage that has been registered must be followed by making APHT no later than 1 (one) month after it is given. If the land has not been registered, or has been certified but has not been registered in the name of the mortgagee as a new right holder, the deadline for making APHT is 3 months after it is granted. SKMHT which is not followed by making APHT within the specified time, is null and void. In addition, the SKMHT is only an authorized institution and not as a guarantee institution in paying off a loan. This means that SKMHT does not give any position to the bank as a creditor.